2022
DOI: 10.1039/d1ra08929c
|View full text |Cite
|
Sign up to set email alerts
|

Liquid cooling system for battery modules with boron nitride based thermal conductivity silicone grease

Abstract: Heat-conductive silicone grease (HCSG), one of the most common composite thermal interface materials (TIMs) used in many advanced applications, is limited by its low thermal conductivity (TC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…Boron nitride, which has a unique combination of high heat conductivity and high electrical insulation, is often used in experiments as a filler in TIMs. One experiment showed that using surface-modified spherical boron nitrides (SBNs) reduced maximum temperature [119]. The silicone rubber matrix was also studied to incorporate hexagonal boron nitride (h-BN) as a filler to increase thermal conductivity.…”
Section: Boron Used In Btmsmentioning
confidence: 99%
“…Boron nitride, which has a unique combination of high heat conductivity and high electrical insulation, is often used in experiments as a filler in TIMs. One experiment showed that using surface-modified spherical boron nitrides (SBNs) reduced maximum temperature [119]. The silicone rubber matrix was also studied to incorporate hexagonal boron nitride (h-BN) as a filler to increase thermal conductivity.…”
Section: Boron Used In Btmsmentioning
confidence: 99%
“…The paraffin wax-based composite, with a loading of 20 wt% highly ordered and interconnected hexagonal boron nitride (hBN) networks, shows a thermal conductivity of 1.86 W•m −1 •K −1 , which is four times higher than the similar composite but with the unoriented filler and eight times higher than that of unfilled paraffin [5]. A simple modification of the surface of BN (spherical particles) with SiO 2 , followed by incorporation into epoxy-silicone resin matrix, led to a material with improved thermal conductivity of 3.1 W•m −1 •K −1 , which is about 24% higher than unmodified BN particles and able to support the temperature distribution of a battery module [16]. Due to their very good insulating, mechanical and thermal properties, as well as good adhesion and ease of processing, silicone-based materials are preferred in many applications [17,18].…”
Section: Introductionmentioning
confidence: 96%
“…The obtained composite material was then used to cover prismatic batteries, which has led to an improved heat dissipation [20,21]. A modified silicone-based resin, resulting from adding 1 wt.% spherical boron nitrides, was used as a thermal interface on the surface of the liquid cooling plate of a battery module [22]. It was found that the maximum temperature of the battery module could be maintained within the operational limit of 42 • C, as well as that the temperature difference could be controlled within 5 • C by BTMS.…”
Section: Introductionmentioning
confidence: 99%